Opposite Roles of Tumor Cell Proliferation and Immune Cell Infiltration in Postoperative Liver Metastasis of PDAC - Wang, Guangfu; Dai, Shangnan; Gao, Hao; Gao, Yong; Yin, Lingdi; Zhang, Kai; Huang, Xumin; Lu, Zipeng; Miao, Yi (Frontiers in Cell and Developmental Biology, 2021)
Background Recurrence of liver metastasis after pancreatectomy is often a predictor of poor prognosis. Comprehensive genomic analysis may contribute to a better understanding of the molecular mechanisms of postoperative liver metastasis and provide new therapeutic targets. Methods A total of 67 patients from The Cancer Genome Atlas (TCGA) were included in this study. We analyzed differentially expressed genes (DEGs) by R package “DESeq2.” Weighted gene co-expression network analysis (WGCNA) was applied to investigate the key modules and hub genes. Immunohistochemistry was used to analyze tumor cell proliferation index and CD4+ T cells infiltration. Results Functional analysis of DEGs between the liver metastatic and recurrence-free groups was mainly concentrated in the immune response. The liver metastasis group had lower immune and stroma scores and a higher TP53 mutation rate. WGCNA showed that the genes in key modules related to disease-free survival (DFS) and overall survival (OS) were mainly enriched in the cell proliferation process and tumor immune response. Immunohistochemical analysis showed that the pancreatic cancer cells of patients with early postoperative liver metastasis had higher proliferative activity, while the infiltration of CD4+ T cells in tumor specimens was less. Conclusion Our study suggested that increased immune cell infiltration (especially CD4+ T cells) and tumor cell proliferation may play an opposite role in liver metastasis recurrence after pancreatic cancer.